The competence shield: Fostering competence perceptions weakens the dominance penalty for women in leadership. - Feng, Zhiyu; Ma, Anyi; Dwivedi, Priyanka; Liu, Fangzhou (Journal of Applied Psychology, 2026)
Although research has consistently found that women face social and economic penalties for displaying assertive, dominant agentic qualities often deemed necessary for leadership, limited work has examined how to mitigate the dominance penalty. Integrating the expectation states theory and multidimensional perspectives of agentic perceptions, we found that fostering perceived leader competence attenuated the dominance penalty. Across four studies, including two multiwave, multisource field studies (Studies 1 and 3), a critical incident experiment (Study 2a), and a vignette experiment (Study 2b), we observed the dominance penalty at lower but not higher levels of perceived leader competence. Perceived leader status mediated these effects so that higher (vs. lower) levels of perceived leader dominance led to less favorable leader status and effectiveness evaluations for women (but not for men) leaders, and these gender differences were eliminated at higher levels of perceived leader competence. (PsycInfo Database Record (c) 2026 APA, all rights reserved).